La religión en los tratados internacionales de la monarquía hispánica durante el siglo XVIII - González Cruz, David (2021)
Religion in the international treaties of the Hispanic monarchy during the 18th century: This research addresses the treatment of religious issues in the treaties signed by the Hispanic Monarchy with European nations and Muslim political leaders of the Mediterranean area during the eighteenth century. The study shows the implications of Church-State relations in international accords agreed by the Spanish Crown and the complexity of applying peace adjustments to the transfer of territories to other countries with an official religion different from the Catholic one - as it is the case of Great Britain - as well as the difficulties that were generated for its effective compliance.
Esta investigación aborda el tratamiento de las cuestiones religiosas en los tratados firmados por la monarquía hispánica con las potencias europeas y los líderes políticos musulmanes del área mediterránea durante el siglo XVIII. En el estudio se aprecian las implicaciones de las relaciones Iglesia-Estado en los convenios internacionales pactados por la corona española y la compleji-dad de aplicar los ajustes de paz a la cesión de territorios a otras naciones con una religión oficial diferente a la católica - como es el caso de Gran Bretaña -, así como las dificultades que se generaron para su efectivo cumplimiento.
Keywords: Religión; tratados; Paz; Guerra; católicos; anglicanos; Musulmanes; monarquía; España; Inglaterra; Francia; América; Marruecos; Turquía; Argel; Trípoli; Túnez; Religion; Treaties; Peace; War; Catholics; Anglicans; Muslims; Monarchy; Spain; England; France; Menorca; Gibraltar; America; Morocco; Turkey; Algiers; Tripoli; Tunisia; 18th Century; Siglo XVIII